2020
DOI: 10.1186/s12886-020-01704-6
|View full text |Cite
|
Sign up to set email alerts
|

Age distribution and associated factors of cornea biomechanical parameter stress-strain index in Chinese healthy population

Abstract: Background To investigate the new cornea biomechanical parameter stress-strain index (SSI) in Chinese healthy people and the factors associated with SSI. Methods A total of 175 eyes from 175 participants were included in this study. Axial length was measured with the Lenstar LS-900. Pentacam measured curvature of the cornea and anterior chamber volume (ACV). Cornea biomechanical properties assessments were performed by corneal visual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 47 publications
3
15
2
1
Order By: Relevance
“…In concordance with our previous findings, the SSI of the SEE group was significantly lower than that of the MEE group ( Liu et al, 2020 ). In the MEE group, the SSI was significantly negatively correlated with AL.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In concordance with our previous findings, the SSI of the SEE group was significantly lower than that of the MEE group ( Liu et al, 2020 ). In the MEE group, the SSI was significantly negatively correlated with AL.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding corneal biomechanical measurement technology, the new parameter stress-strain index (SSI) provided by corneal visualization Scheimpflug technology (Corvis ST) can reflect corneal stiffness without being affected by central corneal thickness (CCT) or intraocular pressure (IOP) ( Eliasy et al, 2019 ). One of our previous studies found that the SSI was negatively correlated with AL, but high myopia was not included for that study ( Liu et al, 2020 ). However, the extent of myopia may influence corneal biomechanics ( Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports of these relationship were mixed, the DA was correlated with CCT and IOP (Hon and Lam, 2013;Ali et al, 2014;Huseynova et al, 2014), the DARatio2mm had high correlation with CCT and IOP (Vinciguerra et al, 2016), and the IIR correlated with CCT (Vinciguerra et al, 2016) while not with IOP. In other studies, DA, DARatio2mm, IIR, and SP-A1 were all correlated with CCT and IOP (Sedaghat et al, 2020), CBI was correlated with IOP and CCT (Yang et al, 2019), and SSI was correlated with IOP but not with CCT (Liu et al, 2020). The studies noted above were cross-sectional, and the variation range in both subjects and biometric parameters was large, which may have influenced the correlation results.…”
Section: Discussionmentioning
confidence: 89%
“…SSI is a parameter created for evaluating corneal rigidity that does not depend on bIOP and corneal thickness but depends on age. 26 , 27 The higher the SSI, the higher the corneal rigidity. 28 SSI was calculated using the following formula:…”
Section: Methodsmentioning
confidence: 99%